Answer:
All you need to do is make sure the first expression is solved for y (which it is), and then substitute it into the second expression in place of any occurrences of y:
given the second expression:
x - y = 1
We'll replace y with it's value in the first expression:
x - (y) = 1
x - (5 - 2x) = 1
Now we can expand the resulting equation:
x - 5 + 2x = 1
So <em>neither</em> of the answers provided are correct.
You can then solve for x:
x - 5 + 2x = 1
x - 5 + 5 + 2x = 1 + 5
x + 2x = 6
3x = 6
3x/3 = 6/3
x = 2
After that, you can find y by plugging x into either of the two original equations:
y = 5 - 2x
y = 5 - 2(2)
y = 5 - 4
y = 1
A parabola, a graph of a quadratic function, cannot have a maximum vertex and a minimum vertex at the same time because of the shape of the graph. A parabola is a u-shaped graph. The vertex of the parabola is the point where the u changes direction; if it was increasing, it starts to decrease, and if it was decreasing, it starts to increase. Since a parabola only changes direction once, there will either be a minimum or a maximum, not both.
Answer:
14
Step-by-step explanation:
1. Do the "Two Mark" Rule
- 7 + (+12) - 5
2. Do your addition before subtracting
- 7 + 12 = 19
3. Subtract your remaining two numbers
- 19 - 5 = 14